The origin of B chromosomes in yellow-necked mice (Apodemus flavicollis)-Break rules but keep playing the game. - M Rajičić; S A Romanenko; T V Karamysheva; J Blagojević; T Adnađević; I Budinski; A S Bogdanov; V A Trifonov; N B Rubtsov; M Vujošević (PLoS ONE, 2017)
B chromosomes (Bs) are known for more than hundred years but their origin, structure and pattern of evolution are not well understood. In the past few years new methodological approaches, involving isolation of Bs followed by whole DNA amplification, DNA probe generation, and fluorescent in situ hybridization (FISH) or the B chromosome DNA sequencing, has allowed detailed analysis of their origin and molecular structure in different species. In this study we explored the origin of Bs in the yellow-necked wood mouse, Apodemus flavicollis, using generation of microdissected DNA probes followed by FISH on metaphase chromosomes. Bs of A. flavicollis were successfully isolated and DNA was used as the template for B-specific probes for the first time. We revealed homology of DNA derived from the analyzed B chromosomes to the pericentromeric region (PR) of sex chromosomes and subtelomeric region of two pairs of small autosomes, but lower homology to the rest of the Y chromosome. Moreover, all analysed Bs had the same structure regardless of their number per individual or the great geographic distance between examined populations from the Balkan Peninsula (Serbia) and Eastern Europe (south region of Russia and central Belarus). Therefore, it was suggested that B chromosomes in A. flavicollis have a unique common origin from the PR of sex chromosomes, and/or similar evolutionary pattern.